Variability of size of the upper jaw molars of the population of Krasnoyarsk taking into account the time vector - E. V. Pozovskaya; T. M. Savenkova; S. L. Baksheeva; N. N. Medvedeva (Acta Biomedica Scientifica, 2018)
The article presents the results of the study of odontology of the population characteristics in Krasnoyarsk city of XVII-XXI centuries. The aim of this work is to study the main variability dimensions of the molars of the right upper jaw of the population in Krasnoyarsk city in different time frames. For each object of the study, a map of the odontological examination was completed, including the measurement of the mesiodistal and vestibulooral diameters of the right upper jaw molars in the neck and crown regions of the tooth. Based on the results of the measurements, a comparison was made between the average size of the maxilla molars in the population of the city of Krasnoyarsk, depending on gender and the historical period. 131 skulls from osteological series of necropolises ofKrasnoyarsk (73 skulls - Pokrovsky necropolis, XVII-XVIII centuries, 58 skulls - Vsekhsvyatskiy necropolis, XVIII-XIX centuries) and dento-maxillary system of the modern population (68 people) were studied. A biometric study of the size of the molars of the right upper jaw has shown that over the past centuries, residents of the city of Krasnoyarsk experienced an increase in mesiodistal and vestibulo-oral teeth sizes in both men and women. A statistically significant increase in the mesiodistal diameter of the crown and neck of the 16th and 17th teeth was found in all groups of subjects, a statistically significant change in the vestibulooral size was characteristic only of the crown of the first molar of women.